A non-inferiority study of the clinical effectiveness of anaesthesia obtained via application of a novel topical anaesthetic putty compared to infiltration of Lidocaine for the treatment of lacerations in the emergency department. (26th December 2010) - Jenkins, Mark
Abstract : Introduction: Background: The standard treatment for lacerations in the Emergency Department is to use local anaesthetic to aid cleaning, analgesia and wound repair. The use of topical anaesthesia has not been widely accepted within clinical practice in the UK due to the lack of an appropriate delivery system. A new putty has been developed to deliver topical anaesthesia that can deliver lidocaine and then be removed intact from the wound in its entirety. Aim: To assess the safety and efficacy of new topical Lidocaine putty in anaesthetising lacerations compared with standard Lidocaine injection. A secondary aim was to compare rates of wound infection and dehiscence between two groups. Methods: A non-inferiority randomised controlled trial comparing the anaesthesia obtained following application of topical anaesthetic gel to a laceration for 20 min compared with that obtained 10–15 min after infiltration with 1% w/v Lidocaine into the wound edges. Pain scores were assessed for the wound repair using visual analogue scales. Follow-up information regarding wound infection, wound dehiscence and wound appearance was performed 7–10 days later. Results: Sixty seven patients were recruited. Thirty four were in the Lidocaine gel group and 33 in the Lidocaine infiltration group. Pain scores were collected for both groups: the study group (range 0–7, mean 1.5) and control group (range 0–5, mean 1.1) showed no significant difference (p=0.29). Three patients in the control group required rescue anaesthesia and three patients in the study group required rescue anaesthesia. Two patients in the control group developed wound infection and one patient in the control group had wound dehiscence. In the study group two patients developed wound infection. Conclusion: The use of a new topical anaesthetic putty is as effective for analgesia and wound repair as infiltration with 1% Lidocaine.